Impact of COVID-19 lockdowns on the Employment Status and Income level of Women Domestic Workers in Chennai (International Journal of Food and Nutritional Sciences, 2025)
This study examines the socio-economic impact of the COVID-19 pandemic on women domestic workers in Chennai through a mixed-methods approach. Domestic workers form an essential yet undervalued segment of the city’s informal economy, facing low wages, insecure employment, and limited social protection. The pandemic and ensuing lockdowns magnified these vulnerabilities, leading to widespread job loss, income decline, and social stigma. Quantitative data from 100 respondents revealed that over half experienced temporary unemployment and 80% faced major income reductions. Qualitative interviews highlighted emotional distress, employer mistrust, and exclusion from relief measures. Migrant workers were disproportionately affected due to lack of registration and support networks. Despite hardships, many women demonstrated resilience through mutual aid and informal credit systems. The study underscores the need for inclusive welfare policies, legal recognition, and stronger institutional mechanisms to safeguard domestic workers in crisis situations.